Galectin‐1 is a new fibrosis protein in type 1 and type 2 diabetes. Issue 1 (5th July 2018) - Al-Obaidi, Noor; Mohan, Sumathy; Liang, Sitai; Zhao, Zhenze; Nayak, Bijaya K.; Li, Boajie; Sriramarao, P.; Habib, Samy L.
ABSTRACT: Chronic exposure of tubular renal cells to high glucose contributes to tubulointerstitial changes in diabetic nephropathy. In the present study, we identified a new fibrosis gene called galectin‐1 (Gal‐1), which is highly expressed in tubular cells of kidneys of type 1 and type 2 diabetic mouse models. Gal‐1 protein and mRNA expression showed significant increase in kidney cortex of heterozygous Akita +/− and db/db mice compared with wild‐type mice. Mouse proximal tubular cells exposed to high glucose showed significant increase in phosphorylation of Akt and Gal‐1. We cloned Gal‐1 promoter and identified the transcription factor AP4 as binding to the Gal‐1 promoter to up‐regulate its function. Transfection of cells with plasmid carrying mutations in the binding sites of AP4 to Gal‐1 promoter resulted in decreased protein function of Gal‐1. In addition, inhibition of Gal‐1 by OTX‐008 showed significant decrease in p‐Akt/AP4 and protein‐promoter activity of Gal‐1 and fibronectin. Moreover, down‐regulation of AP4 by small interfering RNA resulted in a significant decrease in protein expression and promoter activity of Gal‐1 . We found that kidney of Gal‐1 −/− mice express very low levels of fibronectin protein. In summary, Gal‐1 is highly expressed in kidneys of type 1 and 2 diabetic mice, and AP4 is a major transcription factor that activates Gal‐1 under hyperglycemia. Inhibition of Gal‐1 by OTX‐008 blocks activation of Akt and prevents accumulation of Gal‐1, suggesting a novel role of Gal‐1 inhibitor as a possible therapeutic target to treat renal fibrosis in diabetes.—Al‐Obaidi, N., Mohan, S., Liang, S., Zhao, Z., Nayak, B. K., Li, B., Sriramarao, P., Habib, S. L. Galectin‐1 is a new fibrosis protein in type 1 and type 2 diabetes. FASEB J. 33, 373–387 (2019). www.fasebj.org